Ecotypic differentiation of leaf silicon concentration in the grass Brachypodium hybridum along a rainfall gradient - Kurze, Susanne; Ouyang, Jinyu; Gade, Florian; Katz, Ofir; Schaller, Jörg; Metz, Johannes (Frontiers in Plant Science, 2024)
Ecotypic differentiation, reflected in substantial trait differences across populations, has been observed in various plant species distributed across aridity gradients. Nevertheless, ecotypic differentiation in leaf silicon concentration, known to alleviate drought stress in plants, remained hardly explored.Here, we provide a systematic test for ecotypic differentiation in leaf silicon concentration along two aridity gradients in the grass Brachypodium hybridum in Israel.Seed material was sampled in 15 sites along a macroclimatic aridity gradient (89 -926 mm mean annual rainfall) and from corresponding north (moister) and south (more arid) exposed slopes (microclimatic gradient) at similar altitudes (mean north: 381 m a.s.l., mean south: 385 m a.s.l.). Plants were subsequently grown under common conditions and their leaf silicon concentration was analysed.Leaf silicon concentration increased with increasing aridity across the macroclimatic gradient, but did not differ between north and south slopes. The higher leaf silicon concentrations under more arid conditions can enhance the ability of plants to cope with more arid conditions by two mutually not exclusive mechanisms: (i) withstanding drought by reducing water loss and increasing water uptake or (ii) escaping drought by facilitating fast growth. Our study highlights that leaf silicon concentration contributes to ecotypic differentiation in annual grasses along macroclimatic aridity gradients.